CEGAH STUNTING DENGAN EDUKASI AIR BERSIH DAN JAMBAN MELALUI PEMBERDAYAAN MASYARAKAT BERBASIS LOCAL WINSDOM - Alfina Baharuddin; Annisa junaid; Ricky Perdana Poetra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Open defecation is one example of unhealthy behaviour. Open defecation is the act of disposing of faeces or faeces in fields, forests, bushes, rivers, beaches or other open areas and is allowed to spread contaminating the environment, soil, air and water. The objectives of this service are: To improve basic sanitation outcomes in Bontomanai Village including: Increasing ownership and utilisation of latrines, increasing understanding of water purification techniques at the household level, increasing local winsdom-based community participation/empowerment related to environmental sanitation towards zero ODF villages. The solutions offered in this service activity are 1. Conducting knowledge transfer education related to healthy latrines according to their functions and benefits for environmental health as well as the practice of making septi tanks and pilot healthy latrines 2. Conducting knowledge transfer education related to water purification methods 3. Conducting local winsdom-based community empowerment. The results of the service showed that there was an increase in the knowledge of the partners from the pre-test activity in the moderate category (83.3%) while for the post-test it increased to 86.6%. There was an increase in the attitude of the partners from the pre-test activity in the sufficient category (80%) while for the post test it increased to 86.6%.There was an increase in the actions of the RT mothers from the pre-test activity in the sufficient category (76.6%) while for the post test it increased to 83.3%. AbstrakPerilaku buang air besar sembarangan (BABS/Open defecation) termasuk salah satu contoh perilaku yang tidak sehat. BABS/Open defecation adalah suatu tindakan membuang kotoran atau tinja di ladang, hutan, semak – semak, sungai, pantai atau area terbuka lainnya dan dibiarkan menyebar mengkontaminasi lingkungan, tanah, udara dan air. Tujuan pengabdian ini adalah: meningkatkan capaian sanitasi dasar di Desa Bontomanai meliputi: Meningkatkan kepemilikan dan pemanfaatan jamban, meningkatkan pemahaman tentang teknik penjernihan air ditingkat rumah tangga., meningkatkan partisipasi /Pemberdayaan masyarakat berbasis local winsdom terkait sanitasi lingkungan menuju desa zero ODF. Solusi yang ditawarkan dalam kegiatan pengabdian ini adalah 1. Melakukan edukasi transfer pengetahuan terkait Jamban sehat sesuai fungsi dan manfaat bagi kesehatan lingkungan serta praktek pembuatan septi tank dam jamban sehat percontohan 2. Melakukan edukasi transfer pengetahuan terkait metode penjernihan air 3. Melakukan perberdayaan masyarakat berbasis local winsdom. Hasil pengbdian menunjukkan Terjadi peningkatan pengetahuan para mitra dari kegiatan pre test kategori cukup (83,3%) sedangkan untuk post test meningkat menjadi 86,6%. Terjadi peningkatan sikap para mitra dari kegiatan pre test kategori cukup(80%) sedangkan untuk post test meningkat menjadi 86,6%.Terjadi peningkatan tindakan para ibu-ibu RT dari kegiatan pre test kategori cukup (76,6%) sedangkan untuk post test meningkat menjadi 83,3%.